PRINCIPLE OF HUMANIZATION AND PSYCHOLOGIZATION OF PEDAGOGICAL MANAGEMENT AS A BASIS PERSONAL-ORIENTED IMPLEMENTATIONS TRAINING DURING THE PROFESSIONAL PROCESS TRAINING OF PEDAGOGICAL STAFF (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the principle of humanismation and psycholigation of pedagogical management during professional training.